Effect of the seawater treatment on the physical properties of oil palm empty fruit bunches filled poly (vinyl alcohol) - Siti Ayu Aziz (2018)
Particularly, Malaysia and Indonesia are stated to be a producer of the most important crops of oil palm. However, most of the residues from the palm plantation are burnt instead of being used efficiently, hence affect the eco-system. As an alternative, oil palm fibre can be used as a filler in biocomposites. The aim of this study is to characterize the mechanical,· chemical, morphological, and thermal e-ffects of the seawater treated of oil palm empty fruit bunch (EFB) single fibres and composites. The optimization period for the seawater treatment were carried out on day-10, day- 20, day-30 and day-40. The seawater used at different geographical areas known as Pulau Tiga and Pulau Gaya. The fibres of oil palm EFB has been treated from day-3 until day-30, the different filler loading of 1 %, 3% and 5% of untreated and treated composites were prepared using casting method. The prepared biocomposites use water-soluble polymer of poly(vinyl alcohol) as a matrix. The mechanical properties of untreated and seawater treated of both single fibres and composites was studied using Universal Tensile Machine (UTM) while the chemical effect were characterized using Fourier Transform Infrared (FT-IR) and the morphological examined using Scanning Electron Microscopy (SEM).The thermal properties of the composites of untreated and seawater treated were analysed using Thermogravimetric Analysis {TGA). Based on the finding, the seawater treated of both single fibres and composites has improved compared to untreated one. The mechanical properties of these a water treated single fibres enhanced at day-30 with increment of 269.3%, while for the composites, the mechanical strength of both islands increased significantly at the optimum filler loading of 1 % than the untreated composites. Based on the thermal effect, Pulau Tiga composites has the good thermal stability due to the highest onset temperature. The morphological changes enhanced with the seawater treatment, however, at the filler loading of 5%, the composites easily cracked with more voids detected. The optimization period of the seawater treatment shows that on day 30 was the optimum period of the seawater treatment for the oil palm EFB fibres, since on day 40, the mechanical properties reduced. In conclusion, seawater treatment significantly improved an extra enhancement in mechanical strength. Thus, the result provides alternatives efficiency method of surface modification by nature as low-priced better and safer than chemicals treatment.